Enhanced recovery programs in lung cancer surgery: systematic review and meta-analysis of randomized controlled trials - Li S; Zhou K; Che G; Yang M; Su J; Shen C; Yu P (Cancer Management and Research, 2017)
Shuangjiang Li,1 Kun Zhou,1 Guowei Che,1 Mei Yang,1 Jianhua Su,2 Cheng Shen,1 Pengming Yu2 1Department of Thoracic Surgery, 2Department of Rehabilitation, Rehabilitation Medicine Center, West China Hospital, Sichuan University, Chengdu, China Background: Enhanced recovery after surgery (ERAS) program is an effective evidence-based multidisciplinary protocol of perioperative care, but its roles in thoracic surgery remain unclear. This systematic review of randomized controlled trials (RCTs) aims to investigate the efficacy and safety of the ERAS programs for lung cancer surgery. Materials and methods: We searched the PubMed and EMBASE databases to identify the RCTs that implemented an ERAS program encompassing more than four care elements within at least two phases of perioperative care in lung cancer surgery. The heterogeneity levels between studies were estimated by the Cochrane Collaborations. A qualitative review was performed if considerable heterogeneity was revealed. Relative risk (RR) and weighted mean difference served as the summarized statistics for the meta-analyses. Additional analyses were also performed to perceive potential bias risks. Results: A total of seven RCTs enrolling 486 patients were included. The meta-analysis indicated that the ERAS group patients had significantly lower morbidity rates (RR=0.64; p<0.001), especially the rates of pulmonary (RR=0.43; p<0.001) and surgical complications (RR=0.46; p=0.010), than those of control group patients. No significant reduction was found in the in-hospital mortality (RR=0.70; p=0.58) or cardiovascular complications (RR=1.46; p=0.25). In the qualitative review, most of the evidence reported significantly shortened length of hospital and intensive care unit stay and decreased hospitalization costs in the ERAS-treated patients. No significant publication bias was detected in the meta-analyses. Conclusion: Our review demonstrates that the implementation of an ERAS program for lung cancer surgery can effectively accelerate postoperative recovery and save hospitalization costs without compromising patients’ safety. A worldwide consensus guideline is urgently required to standardize the ERAS protocols for elective lung resections in the future. Keywords: enhanced recovery after surgery, lung cancer surgery, morbidity, systematic review, meta-analysis